Posthumanist critique and human health: how nonhumans (could) figure in public health research. Issue 3 (27th May 2017) - Friese, Carrie; Nuyts, Nathalie
Abstract: This paper uses bibliometric analysis and critical discourse analysis to explore the rise in research involving nonhumans in public health, and the potential contribution of posthumanist social theory to this growing body of public health scholarship. There has been a sudden and rather marked increase in research and writing on animals, zoonoses and/or the 'One-health' paradigm within public health journals since 2006. Indeed 'One-health' rather than 'posthumanism' holds together research involving nonhumans of various kinds – from viruses to animals – within the discipline. Advocates of the 'One-health' paradigm argue that human and animal health must be integrated through joining the research, training and care practices of human and animal medicine. By mapping the terrain of public health research involving non-human species, we consider how and where posthumanist theory could be productively drawn upon to contribute to both critical and applied research involving nonhumans within public health. We specifically ask how the posthumanist insight to 'follow the nonhumans' would raise new questions and analytics for this research area.